2018
DOI: 10.1002/jcb.27160
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β induces increased tight junction permeability in bovine mammary epithelial cells via the IL‐1β‐ERK1/2‐MLCK axis upon blood‐milk barrier damage

Abstract: Bovine mastitis occurs frequently in dairy cows and is often caused by various aetiological organisms, for example, Escherichia coli. Lipopolysaccharide (LPS) is a key virulence factor of E. coli. In this study, we stimulated bovine mammary epithelial cells (BMECs) with LPS to investigate the global transcriptional response and identify specific proinflammatory factors that play important roles in blood-milk barrier damage during mastitis caused by E. coli. By performing RNA-seq, we identified a large number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…MLCK1 is also known to regulate the intestinal TJ barrier function via phosphorylation of myosin II regulatory light chain (MLC) at threonine-18 and/or serine-19 leading to peri-junctional actomyosin ring contraction, mechanical retraction of apical membrane and pulling apart of the TJ complex, and opening of the intestinal TJ barrier ( 109 , 115 117 ). Previous studies have shown that the IL-1β-induced increase in intestinal epithelial TJ permeability in Caco-2 intestinal epithelial monolayers and mouse small intestine in vivo was mediated by an increase in MLCK gene activity and protein expression and an increase in MLCK enzymatic activity ( 84 ) ( 45 , 46 , 118 120 ). In these studies, IL-1β caused a rapid activation of MLCK gene activity and increase in MLCK protein expression; inhibition of MLCK activity by pharmacologic inhibitors or by siRNA-induced knockdown prevented the IL-1β-induced increase in intestinal epithelial TJ permeability ( 84 , 121 ).…”
Section: Mechanisms Of the Il-1β-induced Modulation Of The Intestinal Tj Barriermentioning
confidence: 99%
“…MLCK1 is also known to regulate the intestinal TJ barrier function via phosphorylation of myosin II regulatory light chain (MLC) at threonine-18 and/or serine-19 leading to peri-junctional actomyosin ring contraction, mechanical retraction of apical membrane and pulling apart of the TJ complex, and opening of the intestinal TJ barrier ( 109 , 115 117 ). Previous studies have shown that the IL-1β-induced increase in intestinal epithelial TJ permeability in Caco-2 intestinal epithelial monolayers and mouse small intestine in vivo was mediated by an increase in MLCK gene activity and protein expression and an increase in MLCK enzymatic activity ( 84 ) ( 45 , 46 , 118 120 ). In these studies, IL-1β caused a rapid activation of MLCK gene activity and increase in MLCK protein expression; inhibition of MLCK activity by pharmacologic inhibitors or by siRNA-induced knockdown prevented the IL-1β-induced increase in intestinal epithelial TJ permeability ( 84 , 121 ).…”
Section: Mechanisms Of the Il-1β-induced Modulation Of The Intestinal Tj Barriermentioning
confidence: 99%
“…Thus LRRC75A may act as receptor on membrane, and overexpression of LRRC75A increases the LRR motif on the cell surface promoting more interaction between bacteria components, such as LPS, and its receptor constructed by LRR domain, triggering more intensified inflammatory response including the activation of NF-κB pathway and more followed secretion of various inflammatory factors, which may explain the result that less bacteria adhere to LRRC75A-AS1 -/cell than control, and the result that down-regulated LRRC75A led to the less activation of NF-κB pathway while overexpressed LRRC75A contributed to the opposite. In addition, high level of inflammatory factors and bacterial toxins can disrupt TJ structure [30,[51][52][53][54]. Based on these previous findings, a theory is proposed that during inflammation, bacterial antigen activates NF-κB pathway, then together with bacterial toxins, a large amount of introduced inflammatory factors results in broken TJ structure.…”
Section: Discussionmentioning
confidence: 99%
“…When mammary tissue is exposed to proinflammatory cytokines during mastitis, highly expressed H19 introduces more intensified inflammatory response of mammary epithelial cells, resulting in a higher level of inflammatory cytokines in the mammary gland to facilitate the clearance of bacteria and their toxic substances timely, meanwhile decrease the stimulus from bacteria by repressing cell adhesion ability. During this process, the upregulation effect on TJ proteins exerted by H19 was covered up by the influence of inflammatory cytokines secretion (Mankertz et al, 2000; Xu et al, 2018). Until the end of inflammation, when the stimulus, such as LPS, was expelled or destroyed, H19 recovery effect started to show up by upregulating the expression of TJ related proteins to rebuild the blood-milk barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation usually causes dysfunction of mammary glands, as Kobayashi confirmed that injection of LPS, the major structural elements of the Escherichia coli ( E. coli ) cell membrane, into the mouse mammary gland could cause the leak of β-casein from mammary alveolar to interstitial, coincided with the damage of tight junction (TJ) structure of mammary epithelial cells in inflammatory conditions (Kobayashi et al, 2013). We have reported that TJ plays a pivotal role in maintaining the integrity of blood-milk barrier in bovine mammary glands under an inflammatory condition in previous publication (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 91%